Paleoseismological analysis of the Palu Segment within the East Anatolian fault system: Implications for seismic hazard assessment - Kocbulut, Fikret; Akgun, Elif; Softa, Mustafa; Kosaroglu, Sinan; Tatar, Orhan (Science Press, 2025)
The Palu segment, situated in the northeastern part of the East Anatolian Fault System (EAFS), is a crucial structural feature with notable seismic potential. This study examines the paleoseismic activity of the Palu segment through trench excavations and geochronological analyses utilizing Optically Stimulated Luminescence (OSL) and radiocarbon (14C) dating methods. Two trenches, located near Kar & scedil;& imath;bah & ccedil;eler, exposed evidence of multiple surface-rupturing seismic events spanning the Holocene and Pleistocene epochs. Chronological analyses identified five distinct seismic events in trench 1 (P1), dated between 94.09 +/- 6.07 ka and 0.84 +/- 0.45 ka, and three events in trench 2 (P2), dated between 28.83 +/- 1.61 ka and 351 +/- 21 BP. Bayesian analysis using Oxcal distribution suggested event timings between 90.52 +/- 25.99 ka and 1.25 +/- 0.55 ka. Comparative analysis with historical earthquake records correlates the most recent event with the 1789 or 1874 AD earthquakes, while the penultimate event matches the 995 AD earthquake. Earlier events reflect prehistoric tectonic activity. The recurrence intervals for these events range from 710 to 5,370 years during the Holocene, with evidence of seismic activity extending into the Pleistocene. Stress inversion analyses and geodetic data indicate a predominantly strike-slip stress regime, consistent with geometry of the fault. These findings provide critical insights into the long-term seismic behavior and recurrence patterns of the Palu segment, enhancing seismic hazard assessments for the region.
Keywords: Palu segment; East Anatolian fault system; Paleoseismology; Kinematic analysis; Recurrences Interval